AKSARA BATAK DALAM KEBHINNEKAAN NUSANTARA - Nasoichah, Churmatin (Kebudayaan, 2016)
AbstractIn general, Indonesian people and their cultural complex can be seen as a plural andheterogeneous (diverse) relation at the same time. The Indonesianness (Keindonesiaan) isbegin with diversity in the archipelago. The rapid flow of arrival of other cultures triggered theprocess of acculturation and cultural uniformity. Batak, as one of the ethnic groups, is capableto respond creatively to Hindu-Buddhist influences that coming from outside of the archipelagousing the independence of its local culture which is reflected in the form of Batak alphabet. Theformal form of this script is different from other local scripts, but it has a standardized patternof writing through the use of ina ni surat and anak ni surat which derived from the Pallawa. Themain issue that raised is regarding the form of the diversity contained in Batak alphabet. Theaim is to describe the diversity through the alphabet, as well as to increase the repertoire ofdiversity through diverse scripts. The method used in this study is inductive reasoning throughcomparative studies. As a result, Batak scripts and several other local scripts indicate thediversity of script development that happens due to periods and the conditions in their respectivecommunities. The existence of local scripts also indicate a value of cultural diversity in theIndonesian archipelago.Â AbstrakSecara umum masyarakat Indonesia beserta kompleks kebudayaannya dapat dilihat sebagaisuatu relasi yang bersifat plural (jamak) sekaligus heterogen (aneka ragam). Ke-Indonesia-anberawal dari keberagaman atau kebhinnekaan di Nusantara. Kedatangan arus deras budaya dariluar memicu adanya proses akulturasi budaya dan penyeragaman budaya Nusantara. Bataksebagai suatu etnis yang terdapat di Nusantara, melalui kemandirian budaya lokalnya mampumenanggapi secara kreatif pengaruh Hindu-Buddha yang datang dari luar yang tercermin dalamsalah satunya berupa aksara Batak. Bentuk formal aksara ini berbeda dengan aksara lokal lain,tetapi memiliki pakem/ standar baku dalam hal penulisannya melalui penggunaan ina ni suratdan anak ni surat yang berinduk pada aksara pallawa. Adapun permasalahan utama yangdiajukan berkaitan dengan wujud kebhinnekaan yang terdapat pada aksara Batak. Tujuannyaadalah menggambarkan kebhinnekaan melalui aksara, serta menambah khasanah kebhinnekaanmelalui keragaman aksara. Metode yang digunakan berupa penalaran induktif melalui studikomparatif. Hasilnya, aksara Batak dan beberapa aksara lokal lainnya menunjukkan adanyakebhinnekaan dari perkembangan aksara yang terjadi karena faktor waktu dan kondisi dilingkungannya masing-masing. Adanya beberapa jenis aksara lokal ini juga menunjukkanadanya suatu khazanah keragamanan budaya yang ada di Nusantara.